Fiscal transfers and economic convergence - Jo\~ao Capella-Ramos; Cristina Checherita-Westphal; Nadine Leiner-Killinger (European Central Bank (ECB), 2020)
Before the outbreak of the coronavirus (COVID-19) pandemic, discussions were already taking place on how to complete Economic and Monetary Union (EMU) and increase its resilience, inter alia, by speeding up economic convergence. The impact of the current unprecedented crisis on the euro area economy has given the debate new impetus. As a contribution to this topic - and without going into details of new mechanisms for crisis resolution - this paper analyses the role of fiscal transfers in real and business cycle convergence at a regional level. The paper distinguishes between net fiscal transfers - a broad measure defined as the ratio between disposable and primary incomes - and EU structural and investment funds. It provides evidence that net fiscal transfers have contributed to income redistribution across regions and to faster convergence in disposable incomes, although not to higher economic growth and real convergence. More positive evidence has been found for the role of the EU structural and investment funds over the medium term, based on the newly available - and richest so far - European Commission database. Going forward, in addition to efficiency considerations, which are important for real convergence, recommendations on the size and allocation of fiscal transfers should account for their impact on the business cycle. At the same time, in the longer run, it should be borne in mind that fiscal transfers are no substitute for genuine structural reforms and sound macroeconomic and fiscal policies when it comes to promoting sustainable economic growth and convergence.
Keywords: H54; H77; O47; 330; Fiscal transfers; EU structural and investment funds; real convergence; business cycle convergence; economic growth; business cycle